Ambidexterity in projects: An intellectual capital perspective. Issue 1 (January 2015) - Turner, Neil; Maylor, Harvey; Swart, Juani
Abstract We identify the desirability of simultaneously using knowledge assets both to exploit and explore (ambidexterity) and highlight the significance of this for the project context. We use an intellectual capital perspective and theorise that managing projects draws upon human, social and organisational capital. We examine how this is used by managers, in a qualitative study in technology projects, to explain better how ambidexterity is achieved. Ambidexterity in the use of knowledge assets is shown to exist in the practices of managers but without them necessarily having a conscious strategy for it. We identify the mechanisms by which this happens and note the distinctive role of social capital. We demonstrate the integrative nature of the mechanisms, and how each mechanism can involve the deployment of either single or multiple elements of intellectual capital. In so doing we extend the existing theory to the operational level and demonstrate the utility of this approach.